Why Surface Reading Is Not Enough: Morolf, the Skin of the Jew, and German Medieval Studies. (June 2014) - P, S S.
Abstract : This essay makes a case for the continued necessity and usefulness of so-called "symptomatic reading" within the context of German medieval studies. To demonstrate this necessity, the essay focuses on a short episode at the beginning of the medieval German minstrel epic Salman und Morolf in which Morolf, brother of Salman, the Christian king of Jerusalem, disguises himself in the skin of a murdered Jew in order to retrieve Salman's wife Salme, who has been kidnapped by a heathen king. Because the "surface" of the text offers no specific comment on how the episode should be received, solving the puzzles it elicits is only possible by a reading that takes into full account things like historical context (the crusade milieu) and interpretive tools like repression and projection. Using these tools, the essay articulates how the episode operates in relation to the fraught status of the Jew in both Germany and the Middle East. As a conclusion, the essay then offers a broader reading of the epic in which the figure of the disloyal pagan queen represents the elusive quality of the Holy Land vis-à-vis Western sovereignty.